2018
DOI: 10.1089/aivt.2017.0042
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study for the Comparison ofIn VitroData Across Multiple Aerosol Exposure Studies with Extrapolation to Human Dose

Abstract: In vitro aerosol systems offer advantages in generating aerosols and exposing cell cultures at the air-liquid interface (ALI), mimicking human exposure. However, dilution technologies, principles, and characteristics of exposure chambers differ between systems. In addition, various cell types and biological end points can be assessed, meaning that in vitro aerosol data are presented in different ways, so researchers are unable to compare data between systems, studies, and laboratories. In this case study we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…3 Thorne et al took this one step further in a case study and demonstrated that delivered dose and biological response can be compared across systems if a consistent measure of exposure was used to normalize data. 27 Underpinning these steps, individual system characterizations which ensure that these systems are fully understood and detailed in regard to their application and nuances must be conducted by each laboratory. To some extent, validation of these systems are ongoing with pre-validation efforts made with individual system characterizations, which appear to be more common place than interlaboratory efforts.…”
Section: Discussionmentioning
confidence: 99%
“…3 Thorne et al took this one step further in a case study and demonstrated that delivered dose and biological response can be compared across systems if a consistent measure of exposure was used to normalize data. 27 Underpinning these steps, individual system characterizations which ensure that these systems are fully understood and detailed in regard to their application and nuances must be conducted by each laboratory. To some extent, validation of these systems are ongoing with pre-validation efforts made with individual system characterizations, which appear to be more common place than interlaboratory efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated this concept successfully, by bridging data across studies and systems. 19,39 This concept is especially important in the world of next generation tobacco products, such as heated tobacco products and e-cigarettes (ENDS), due to their increasing popularity. Exposure systems are diversifying even further from the ones investigated here, so establishing a strategy to compare between studies and systems is even more important.…”
Section: Discussionmentioning
confidence: 99%
“…Any strategy for comparing across independent studies must therefore factor in the variability of cell line choice and its impact on results, both in variability and the outcome. A recent study 39 examined just this concept, and demonstrated that different continuous cell lines BALB/C and H292 gave the same response in cytotoxicity on different whole aerosol exposure systems when normalised for delivered dose (mass mg/cm 2 and nicotine mg/ml). The study further demonstrated that two different 3D cell systems (MucilAir TM and EpiAirway TM ) gave the similar results when normalised to mass and nicotine (mass mg/cm 2 and nicotine mg/ml) for a cytotoxicity endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…118 Several studies illustrate the value of these systems, which can be found in the papers by Thorne who provided a comprehensive review of the major tobacco smoke exposure systems available to 2013, 118 and a comparison of in vitro data across multiple smoke exposure studies using reference cigarettes and considering three different smoking machines. 119 In the latter review, Thorne demonstrated that in vitro dosimetry techniques can align data between contrasting setups and experimental protocols, resulting in a link between in vitro, in vivo, and human dosimetry studies.…”
Section: Commercial Aerosol and Smoke Exposure Devicesmentioning
confidence: 99%